AISYIYAH DA'WAH MANAGEMENT IN BUILDING THE IDENTITY OF YOUNG WOMEN IN MEDAN BELAWAN - Nabila Putri Amanda; Mailin (Pena Cendekia Insani, 2025)
This research is motivated by the need to understand the role of Aisyiyah's da'wah management, as a Muhammadiyah women's organization, in building the Islamic identity of young women. The aim of this research is to analyze the implementation of Aisyiyah’s da’wah management in shaping the identity of young women in Medan Belawan. This study employs a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews, and document analysis. The results of the study, encompassing planning, organizing, implementation, and evaluation, show that Aisyiyah is capable of designing well-directed programs that align with the needs of young women, such as religious study sessions, mentoring, skills training, and other spiritual activities. These programs are supported by strong organizational structures, the involvement of young cadres, and collaboration with the local community. In its implementation, Aisyiyah employs bil lisan methods through engaging speakers, actively involving young women in discussions and group activities. Evaluation is conducted through special meetings involving the implementation team, where feedback in the form of suggestions and criticisms from participants is gathered to improve future programs.